Assessing the Impact of Facility Layout Design over the Process Productivity and Costs - Saenz, Jose (2009)
Growing variability of markets has helped facility layout design emerge as an improvement tool for companies to facilitate their internal operations and cope with the increasing uncertainty. This is the case of many industries, especially commodities industries.